Pendampingan Penggunaan Aplikasi FlexClip dalam Menyusun Video Animasi bagi Guru di SMK Swasta Kesehatan Darussalam Lhokseumawe - Mahsa, Masithah; Maulidawati, Maulidawati; Ginting, Reza Pahlevi; Rasyimah, Rasyimah (Jurnal Abdi Mas Adzkia, 2024)
Teachers are required to always be ready and responsive in following technological developments in the field of education. One of them is providing the latest learning media and in accordance with learning needs. However, facts in the field show that so far the learning media used has not attracted students' interest in learning. The aim of this activity is to overcome this problem through assistance in using the FlexClip application in compiling animated videos at the SMK Swasta Kesehatan Darussalam Lhokseumawe. This activity is divided into three stages, namely preparation, implementation, and monitoring and evaluation. Meanwhile, the participants in the activity were twenty teachers at the SMK Swasta Kesehatan Darussalam Lhokseumawe. This activity received a positive response from the teacher because after participating in the mentoring activity the teacher was able to use the FlexClip application to compose animated videos as a means of explaining complex concepts in a more visual and interesting way for students.